Biological plausibility of the relationship between chronic periodontitis and ischemic stroke - María Elena González Díaz (Revista Cubana de Estomatología, 2019)
Introduction: True periodontal pockets are an important reservoir of gram-negative bacteria which may exert an influence on distant sites in a variety of manners, bringing about systemic alterations such as diseases derived from atherosclerosis. Objective: Explain the theoretical foundations supporting the proposal of chronic periodontitis as a risk factor for ischemic stroke. Content: 1) Atherosclerosis and cerebrovascular disease, an overview of their pathogenesis. 2) The periodontal microbiota, bases for its association with atherosclerosis and ischemic stroke. Topic presentation: Inflammation is an element of vital importance in all the stages of the atherosclerotic process, be it its onset, progress or complications. By their nature, chronic immunoinflammatory periodontal diseases and the associated anaerobic subgingival infection, constitute a metastatic injury that produces and spreads inflammatory mediators leading to atherosclerosis and participating in the colonization and rupture of atheromatous plaques, which are processes involved in the pathogenesis of ischemic stroke. Final considerations: Better knowledge about the risk relationship between chronic periodontitis and ischemic stroke would allow a rational use of strategies for the prevention and treatment of cerebrovascular disease based on detection of inflammatory processes such as chronic periodontal conditions.